Evaluation of Chemical Fungicides for Managing ChiliAnthracnose Disease Caused by Colletotrichum capsici (Journal of Agriculture and Biology, 2025)
Chili anthracnose, caused by Colletotrichum capsici, is a major disease affecting chili production in Punjab, Pakistan, leading to significant yield losses. This study aimed to isolate and identify the pathogen and evaluate the efficacy of six fungicides at different concentrations (200, 400, 600 ppm) under in-vitro, in vivo, and field conditions. Pathogen isolation and pathogenicity were confirmed through morphological characterization and Koch’s postulates. Fungicide evaluation revealed that Topsin M (thiophanate-methyl 70% w/w) was the most effective, reducing fungal growth to 5.05 mm in vitro and lesion sizes to 10.8 mm and 8.2 mm under greenhouse and field conditions, respectively, at 600 ppm. Fossil (mancozeb 50% w/w) followed closely in efficacy. Other fungicides showed moderate to low disease suppression. Disease severity increased over time, but Topsin M consistently maintained superior control. These findings underscore the potential of Topsin M as a key component in anthracnose management, while highlighting the need for integrated strategies combining chemical, resistant varieties, and biological controls for sustainable disease suppression. This research contributes valuable data for optimizing fungicide use and minimizing economic losses in chili production.